Access to Information for Prisoners - Chacón Alvarado, Lucía (1993)
The purpose of this article is to discuss the importance of prison libraries as an educational and rehabilitative institution, the right of prisoners to library services, the barriers affecting access to information and, finally, the censorship of this type of institution.